Costs and performance of irrigation projects: a comparison of Sub-Saharan Africa and other developing regions - Inocencio, Arlene B.; Kikuchi, M.; Tonosaki, M.; Maruyama, A.; Merrey, Douglas J.; Sally, Hilmy; Jong, J. de (International Water Management Institute, 2007)
High irrigation investment costs together with declining world prices for food and the failures of a number of high profile past irrigation projects are the main reasons for the reluctance of development agencies and governments in Sub-Saharan Africa to invest more resources in irrigation. This study aims to systematically establish whether costs of irrigation projects in Sub-Saharan Africa are truly high, determine the factors which influence costs and performance of irrigation projects, and recommend cost-reducing and performance-enhancing options to make irrigation investments in the region more attractive. It analyzes 314 irrigation projects implemented from 1967 to 2003 in 50 countries in Africa, Asia, and Latin America funded by the World Bank, African Development Bank and the International Fund for Agricultural Development.